Cuba's Basic Units of Cooperative Production - José Alvarez (EDIS)
One of the most important policies of the 1990s was perhaps terminating the state monopoly on land to establish the Basic Units of Cooperative Production (Unidades Básicas de Producción Cooperativa, UBPCs) on those lands. This change is especially significant from a philosophical point of view when one considers that Fidel Castro had consistently referred to state farms and CPAs as “superior forms of agricultural production.” This fact sheet explains how these new forms of agricultural organization were established, how they work, and how they have performed in the ensuing years. This is EDIS document FE487, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published July 2004.